DISTRIBUTION PATTERNS AND POPULATION DENSITY OF GASTROPODS Terebralia sulcata IN ESTUARY OF PUTERI SEMBILAN RUPAT UTARA SUBDISTRIC - Nasution, Syafruddin; Yoswaty, Dessy; ', Maryanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis study was conducted in July 2014, located in the Putri Sembilan estuaryDistrict of Rupat Utara. Mangrove snails of T. sulcata as one of the foods favored ofRupat Utara coastal communities. This research aims to determine the patterns ofdistribution and population density of gastropods T. sulcata in estuary waters PutriSembilan District of Rupat Utara. The method used in this study was a surveymethod and determination of observation stations was determined by purpossivesampling method, where the location of the study divided into three stations. Theresults showed that the highest density of T. sulcata found at Station 2 which locatedat area of mangrove (Â± 100 meters from the station 1 towards the upper river) whilethe lowest density was found at station I (the mouth of the estuary of the river). Thedistribution pattern of mangrove snails T. sulcata overall was evenly which rangesfrom 0,01 - 0,05.Key words: T. sulcata, density, distribution patterns, Rupat Island.